Project management / Siti Jasmeen Mohd. Hashim and Hasena Mustafa - Mohd. Hashim, Siti Jasmeen; Mustafa, Hasena (Faculty of Mechanical Engineering, 1993)
The project that we did was ''PROJECT MANAGEMENT" with a case study that is WINDSOR PHARMACEUTICAL on applications and techniques.. The case study describes how an organization has recently won approval a hair-growth compound and is planning to introduce it before other competitors launch similar products. A project was appointed in the development of a detailed plan for the project. This comprises an activity list, crew sizes and costs. In the introduction section, the project objectives and area/research are described. The second chapter describes an OVERVIEW TO PROJECT MANAGEMENT which include the concepts and some terms often mentioned in project management. PROJECT MANAGEMENT INFORMATION SYSTEM or known as PMIS is a section which describes a little bit about the history of computer in project management, the packages and also on evaluating PMIS.